Manajemen Inovatif Sarana dan Prasarana Sekolah dalam Meningkatkan Kualitas Pembelajaran Digital - Warsito; Hanif, Muh. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the innovative management of school facilities and infrastructure in improving the quality of digital learning at MI Ma'arif NU 01 Pandansari. The research employs a descriptive qualitative approach with data collected through observation, in-depth interviews with principals, teachers, and school committees, as well as documentation of facility inventories and teacher training reports. The findings indicate that innovative management of facilities and infrastructure is implemented through technology-based needs planning, optimization of digital device utilization including smart classrooms, interactive projectors, and internet networks, as well as the development of a learning environment that adapts to technological advancements. The principal acts as a transformational leader and innovator by integrating technology into the learning process and involving teachers and educational staff in collaborative management. The implementation of this innovative management has successfully enhanced students' learning motivation, the effectiveness of online learning, teachers' digital competencies through continuous training programs such as Google Classroom, Canva, and Kahoot, as well as strengthening community participation in facility maintenance. Therefore, innovative management of facilities and infrastructure serves as a strategic factor in improving the quality of digital learning in Islamic elementary schools while maintaining religious values.